Diffuse Partial Woolly Hair in a Patient with Epidermolysis Bullosa Simplex with Mottled Pigmentation - Gerkowicz, Agnieszka (Medknow Publications & Media Pvt Ltd, 2014)
Diffuse partial woolly hair (DPWH) is an uncommon pilar dysplasia defined by the presence of two hair shaft populations with wooly hairs distributed diffusely among normal hairs throughout the scalp. So far the condition has been reported as an isolated disorder with familial occurrence. We report a case of DPWH in 35-year-old female patient with epidermolysis bullosa with mottled pigmentation.